2021
DOI: 10.3389/fvets.2021.758488
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles of lncRNA Following LPS-Induced Inflammation in Bovine Mammary Epithelial Cells

Abstract: Bovine mastitis is an inflammatory response of mammary glands caused by pathogenic microorganisms such as Escherichia coli (E. coli). As a key virulence factor of E. coli, lipopolysaccharide (LPS) triggers innate immune responses via activation of the toll-like-receptor 4 (TLR4) signaling pathway. However, the molecular regulatory network of LPS-induced bovine mastitis has yet to be fully mapped. In this study, bovine mammary epithelial cell lines MAC-T were exposed to LPS for 0, 6 and 12 h to assess the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…LPS is a key virulence factor of Escherichia coli (E. coli) that triggers innate immune responses via activation of the toll-like receptor 4 signaling pathway ( 39 ). To identify, whether E. coli contributes to activating the LPS, the batch cultivation for E. coli was carried out in Luria broth (LB) medium at 37°C with a 2-L working volume.…”
Section: Methodsmentioning
confidence: 99%
“…LPS is a key virulence factor of Escherichia coli (E. coli) that triggers innate immune responses via activation of the toll-like receptor 4 signaling pathway ( 39 ). To identify, whether E. coli contributes to activating the LPS, the batch cultivation for E. coli was carried out in Luria broth (LB) medium at 37°C with a 2-L working volume.…”
Section: Methodsmentioning
confidence: 99%
“…Mumtaz et al [ 134 ] identified 112 differentially expressed lncRNAs in goat mammary epithelial cells induced by E. coli and S. aureus . In addition, Wang et al [ 135 ] also found 112 differentially expressed lncRNAs in LPS-treated bovine mammary epithelial cells, and these lncRNAs participated in inflammation-related signal pathways (i.e., the Notch, NF-κB, MAPK, and PI3K-AKT signal pathways). A large amount of the lncRNA information in the present study may provide clues for functional and molecular studies of mammary epithelial cells–bacteria interaction.…”
Section: Role Of Lncrnas In Inflammatory Diseasesmentioning
confidence: 99%
“…With the development of molecular biology, biostatistics, molecular genetics and marker-assisted breeding technology in recent years, assisted breeding using experimental methods of molecular biology is becoming a new and feasible breeding method [10,11]. The Molecular breeding of dairy cattle has centered around the balanced breeding concept in which functional traits such as reproduction, body shape, health and longevity [12,13] are incorporated into the breeding program. Identifications of genes and genetic markers relevant to milk production are expected to accelerate genetic analysis and breeding programs [14].…”
Section: Advances In Molecular Breeding Of Chinese Dairy Cowsmentioning
confidence: 99%
“…At present, the research on the factors and pathways related to the regulation of inflammation at the molecular level is increasing. A combination of bioinformatics analysis and mechanistic studies has found by Wang et al that target genes of long non-coding RNAs (lncRNA), tcon_00039271 and tcon_00139850, regulated inflammation-related signaling pathways (Notch, NF-κb, MAPK, PI3K-Akt and mTOR) and affected susceptibility to Escherichia coli-induced mastitis [13]. Furthermore, micro-RNAs, miR-320a, miR-19a, miR-19b, miR-143, miR-205 and miR-24, may be blood biomarkers for Staphylococcus aureus-induced mastitis [22].…”
Section: Inflammatory Response and Stress Resistancementioning
confidence: 99%